2006
DOI: 10.1074/jbc.m605532200
|View full text |Cite
|
Sign up to set email alerts
|

A Model for the Proteolipid Ring and Bafilomycin/Concanamycin-binding Site in the Vacuolar ATPase ofNeurospora crassa

Abstract: The vacuolar ATPase has been implicated in a variety of physiological processes in eukaryotic cells. Bafilomycin and concanamycin, highly potent and specific inhibitors of the vacuolar ATPase, have been widely used to investigate the enzyme. Derivatives have been developed as possible therapeutic drugs. We have used random mutagenesis and site-directed mutagenesis to identify 23 residues in the c subunit involved in binding these drugs. We generated a model for the structure of the ring of c subunits in Neuros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
62
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 55 publications
4
62
0
2
Order By: Relevance
“…Other than these differences, comparison of the two states reveals only minor conformational changes in individual subunits, suggesting little flexibility in the enzyme as a whole (Movie S3). The T. thermophilus V/A-ATPase thus seems to be relatively rigid compared with the S. cerevisiae V-ATPase (8) Numerous studies, many by Forgac and coworkers, have investigated the topology, function, and subunit arrangement of the S. cerevisiae V-ATPase V O region (31,34,(38)(39)(40)(41)(42)(43)(44). The model of the a subunit presented here is in excellent agreement with these studies.…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…Other than these differences, comparison of the two states reveals only minor conformational changes in individual subunits, suggesting little flexibility in the enzyme as a whole (Movie S3). The T. thermophilus V/A-ATPase thus seems to be relatively rigid compared with the S. cerevisiae V-ATPase (8) Numerous studies, many by Forgac and coworkers, have investigated the topology, function, and subunit arrangement of the S. cerevisiae V-ATPase V O region (31,34,(38)(39)(40)(41)(42)(43)(44). The model of the a subunit presented here is in excellent agreement with these studies.…”
Section: Resultssupporting
confidence: 72%
“…Finally, studies of the a and c subunits identified residues that, when mutated, can lead to partial resistance to bafilomycin, an inhibitor of V-ATPases. Single and double mutants were made in the c subunit of Neurospora crassa, a mold whose c subunit sequence is 79% identical to that of the S. cerevisiae c subunit (43). Ten residues were proposed to participate in bafilomycin binding, all of which are conserved in S. cerevisiae.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We next used an orthogonal chemical approach to assess the role of V-ATPase function in sensitizing T. brucei to ISM. Bafilomycin is a specific inhibitor of the V-ATPase that binds to the c subunit of V o (22). As predicted, and as demonstrated using isobologram analysis, bafilomycin strongly antagonizes ISM action (Fig.…”
Section: V-atpase Function Sensitizes T Brucei To Ism: Genetic and Cmentioning
confidence: 76%
“…Our data is compatible only with a single binding site per monomeric enzyme. Since concanamycin A most likely binds to intramembranous subunits Whyteside et al 2005;Bowman et al 2006;Dixon et al 2008), the present result suggests that an interaction with a single subunit c is not sufficient for concanamycin A binding: it either binds to more than one subunits or it binds to either subunit a, c' or c" (Huss et al 2002), of which there are only one copies in the structure, although its interaction with the lobster c ring and other recent data Bowman et al 2006;Dixon et al 2008) argue against c' and c'' being the binding sites. The accuracy of our approach could be further improved by adding more points to the inhibitor titration curve.…”
Section: Discussionmentioning
confidence: 99%